NATURAL ASSETS IN GLACIALIZED AREAS AND THE USE OF GIS FOR THE VALORIZATION OF HIGH-MOUNTAIN REGIONS - Diolaiuti, Guglielmina; Smiraglia, Claudio; Pelfini, Manuela; D’Agata, Carlo; Caccianiga, marco (Alpine and Mediterranean Quaternary, 2005)
G. Diolaiuti et al., Natural assets in glacialized areas and the use of gis for the valorization of high-mountain regions. (IT ISSN 0394-3356, 2005). The paper presents the preliminary results obtained through an experimental project focused on the use of GIS software to manage environmental data surveyed in a sample area in the high Italian Alps (Val Viola Bormina, SO). The processing of the data (collected from field surveys with the GPS RTK technique and from aerial photogrammetry analysis) made it possible to obtain geomorphological and vegetational maps (1:10.000 scale). The environmental assets were identified in the sample area through the application of some floristic indices to the vegetational data and a national sheet for the identification and the evaluation of GEOSITES (according to the international UNESCO protocol) applied to the surveyed geomorphological evidences. These assets were called “high-quality floristic and vegetational zones” in the case of the botanical assets and “geomorphological sites or geomorphosites” for the geomorphological assets. The identification of the environmental assets represents the first phase of a valorisation and tourism-promotion project regarding high mountain areas. Some naturalistic educational trails were prepared for this purpose. They suggest some locations for tourists to stop and observe the main environmental features of the natural landscape (both germorphosites and high-quality floristic and vegetational zones). The trails are reported in the GIS on a specific layer and the linked browser also contains logistic information (time needed to reach the trail, difficulty level, hut presence, etc.) useful for organizing the trip. An advantage of the system is that users can make queries (by using the browser and/or the links on the thematic maps) to obtain information or to make changes and variations in the trail route (for instance adding new stops in the vicinity of some of the geomorphological or botanical evidences reported on the maps, but perhaps not included along the suggested trail route). This feature makes the system flexible, serving also for school use (for preparing a school trip or taking a virtual tour of the mountain region before the real trip in the field). The distribution of this product will take place through some computer points located close to the mountain regions studied and by means of an open-source CD-ROM.